The Safety and Efficacy of Nanosecond Pulsed Electric Field in Patients With Hepatocellular Carcinoma: A Prospective Phase 1 Clinical Study Protocol - Xu, Min; Xu, Danxia; Dong, Gang; Ren, Zhigang; Zhang, Wu; Aji, Tuerganaili; Zhao, Qiyu; Chen, Xinhua; Jiang, Tian’an (Frontiers in Oncology, 2022)
Background Hepatocellular carcinoma (HCC) is a highly aggressive malignancy. Irreversible electroporation (IRE) is an ablative modality that uses high-voltage electrical pulses to permeabilize the cell membrane leading to cell necrosis. Unlike traditional thermal ablation, IRE is hardly affected by the “heat-sink” effect and can prevent damage of the adjacent vital structures. Nanosecond pulsed electric field (nsPEF) is a new IRE technique using ultra-short pulses (nanosecond duration), can not only penetrate the cell membranes, but also act on the organelles. Sufficient preclinical researches have shown that nsPEF can eliminate HCC without damaging vital organs, and elicit potent anti-tumor immune response. Objective This is the first clinical study to evaluate feasibility, efficacy, and safety of nsPEF for the treatment of HCC, where thermal ablation is unsuitable due to proximity to critical structures. Methods and analysis We will conduct an open-labeled, single-arm, prospective, multicenter, and objective performance criteria trial. One hundred and ninety-two patients with HCC, in which the tumor is located immediately (<0.5 cm) adjacent to the portal vein, hepatic veins, bile duct, gastrointestinal tract, or diaphragm, will be enrolled among 4 academic medical centers. The primary outcomes are the rate of complete ablation at 1 month and adverse events. Secondary outcomes include technical success, technique efficacy, nsPEF procedural characteristics, local tumor progression, and local progression-free survival. Ethics and dissemination The trial will be conducted according to the ethical principles of the Declaration of Helsinki and has been approved by the ethics committee of all participating centers. The results of this study will be published in peer-reviewed scientific journals and presented at relevant academic conferences. Conclusions This study is the Phase 1 clinical trial to evaluate the efficacy and safety of nsPEF in patients with HCC at high-risk locations where thermal ablation is contra-indicated. The results may expand the options and offer an alternative therapy for HCC. Clinical Trial Registration ClinicalTrials.gov, identifier NCT04309747.